La storia di Ludwig Wittgenstein e di Lev Tolstoj nei “miti” e nelle “immagini” del Novecento - Kuzmenko, Ekaterina (Scenari, 2021)
The article introduces a brief discussion of the main results of the research “The History in ‘Myths’, ‘Images’, and ‘Perspectives’ of the Twentieth century” conducted at the Scuola Normale of Pisa in 2012-2017. The article provides some points of reflection on the criteria of historic “truth” and, in particular, of its “linguistic” interpretation. The rediscovery of the human mental activities contributes along with other philosophical movements (representatives of hermeneutics) to expand traditional definitions of historical research, and to open up the path to the collective mental representations, and to their own understanding.